The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1192/bjp.2018.255
|View full text |Cite
|
Sign up to set email alerts
|

Aiding the diagnosis of dissociative identity disorder: pattern recognition study of brain biomarkers

Abstract: BackgroundA diagnosis of dissociative identity disorder (DID) is controversial and prone to under- and misdiagnosis. From the moment of seeking treatment for symptoms to the time of an accurate diagnosis of DID individuals received an average of four prior other diagnoses and spent 7 years, with reports of up to 12 years, in mental health services.AimTo investigate whether data-driven pattern recognition methodologies applied to structural brain images can provide biomarkers to aid DID diagnosis.MethodStructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 53 publications
2
34
0
7
Order By: Relevance
“…Hence, the current study provides evidence for targeting traumatization as a key predictor of dissociation in individuals with DID. The costs of under-diagnosing DID are high, not only for the individual patients, but also for their residing support system and society as a whole (Reinders et al, 2019). Sleep disturbances are an indicator of mental health suffering (Anderson & Bradley, 2013), but we propose that in DID sleep disturbances are likely to occur as a symptom due to the resurfacing of traumatic childhood experiences, not as causation of DID.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Hence, the current study provides evidence for targeting traumatization as a key predictor of dissociation in individuals with DID. The costs of under-diagnosing DID are high, not only for the individual patients, but also for their residing support system and society as a whole (Reinders et al, 2019). Sleep disturbances are an indicator of mental health suffering (Anderson & Bradley, 2013), but we propose that in DID sleep disturbances are likely to occur as a symptom due to the resurfacing of traumatic childhood experiences, not as causation of DID.…”
Section: Discussionmentioning
confidence: 89%
“…The current study shows that traumatization is the most important predictor of dissociation in individuals with DID and we assume that sleep disturbances are likely to be related to nightmares due to traumatic childhood experiences. A diagnosis of DID is still controversial (Reinders et al, 2019). When an individual presents with severe dissociative symptoms as well as sleeping problems, we recommend to check for nightmares and investigate the origin of sleep disturbances and to explore a trauma-related disorder, such as DID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing evidence base of neurobiological studies supports DID's validity. A study by Reinders et al (2019) found that researchers could discriminate between people with and without DID on the basis of neuroimaging biomarkers with a sensitivity of 72% and specificity of 74%. Blihar et al (2020) completed a systematic review of neuroanatmoical findings in DID demonstrating that people with DID had differences in brain imaging and neural responses compared with controls.…”
Section: Dissociative Disordersmentioning
confidence: 99%
“…Ada kalanya ada satu kepribadian primer dan tindakan klinis umumnya dikhususkan bagi kepribadian primer (Delmonte, Lucchetti, Moreira-Almeida, & Farias, 2016;Laddis, Dell, & Korzekwa, 2017;Reinders et al, 2019;Vissia et al, 2016). (Harymawan, 1986).…”
Section: Pendahuluanunclassified